Hematomyelia Akibat Traumatic Lumbar yang Menyebabkan Syok Spinal: Sebuah Laporan Kasus - Raden Andi Ario Tedjo; Lawly Arrel Dionnie Greatalya; Vivienne Tjung; Muhammad Hafizhan; Stefanus Erdana Putra; Suroto Suroto; Diah Kurnia Mirawati; Subandi Subandi; Rivan Danuaji; Pepi Budianto; Yetty Hambarsari; Baarid Luqman Hamidi; Hanindia Riani Prabaningtyas; Ervina Arta Jayanti Hutabarat; Ira Ristinawati; Teddy Tejomukti (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Spinal cord hemorrhage or hematomyelia can arise from trauma or non-trauma causes, adverse effect of anticoagulation therapy and ruptured vascular malformation. Bleeding in epidural space is common and complications such as acute spinal cord syndrome can arise due to the compression and destruction of the spinal cord. Symptoms of hematomyelia might be varied depending on location of the lesion, often accompanied with acute radicular pain. In this case study, we reported a case of spinal shock after traumatic lumbar hematomyelia. Case: A 13-year-old girl presented to Dr. Moewardi General Hospital with inferior paraparesis, bladder and bowel incontinence, a day after falling on her gluteus. Physical examination revealed reduced motoric and sensory function below 12th thoracal dermatome, with no patellar and reduced Achilles reflexes. Conventional X-ray was unremarkable and further investigation with MRI showed a hematoma on thoracal 10 to 12 vertebrae. Motor and sensory functions were improved after 12 days administration of corticosteroids and further improvement was seen almost immediately after decompression surgery. Objective: To describe a case of spinal shock caused by traumatic lumbar hematomyelia Method: This is a case report study describing spinal shock which improved after administration of corticosteroid and decompression surgery. Conclusion: Spinal shock could be caused by traumatic lumbar hematomyelia, which is characterized by loss of motor, sensory, and bladder function, and decompression surgery improved the prognosis.